DUOLINGO MOBILE ASSISTED LANGUAGE LEARNING (MALL) IN LEARNING ENGLISH VOCABULARY - Syamsuddin, Nur Aziza; Sakkir, Geminastiti; Dollah, Syarifuddin (Universitas Negeri Makassar, 2022)
This research aimed to find out the improvement of Students’ Vocabulary Mastery Through Duolingo as Mobile Assisted Language Learning (MALL). This study involved 32 seventh-grade students from SMPN 1 Pangkajene during the academic year 2022/2023. Classroom Action Research (CAR) was used to carry out the study. This study's data was analyzed using quantitative data from the Pre-test, Post-test Cycle I, and Post-test Cycle II. This study's findings demonstrated that using Duolingo enhanced students' vocabulary mastery scores. The pre-test mean was 45.1, the post-test mean in the first cycle was 60.5, and the post-test mean in cycle II was 88. The percentage of students who passed the Minimum Mastery Criteria-Kriteria Ketuntasan Minimal (KKM) also increased. The pre-test had 5 students (15.6%). In the first post-test cycle, 10 students (31.25%) out of 32 achieved a score of 75 or above. In post-test cycle II, 28 of 32 students (87.5%) received a score of 75 or above. It is possible to infer that Duolingo Mobile Assisted Language Learning (MALL) has significantly enhanced the students' vocabulary knowledge, as seen by the students' significantly increased scores.